Rice carrying capacity and sustainable produce of rice in resources-limited regions - Zhongsheng Guo (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2019)
Rice is a main food over the world. With the growing population and urbanization, the demand for the rice is increasing.To ensure the sustainable produce and market supply of rice is most importantto meet the people's need of rice and the sustainable development. Most of distribution area of rice is in resources-limited regions, and sometime natural calamities infl uences rice yield,quality and market supply almost every year in resources-limited regions over the world. However, there are few reports of rice carrying capacity and sustainable produce of Rice. In this study,author review rice carrying capacity and sustainable produce of rice. In the near future, we should study the rice carrying capacity and regulated the relationship between nature resources and rice plant growth in the resources-limited regions at the right time to ensure the sustainable use of natural resources and sustainable produce of rice and market supply to serve sustainable development.